Factors affect the social engagement among community dwelling older person: community nurses perspective. - Mei Chan, Chong; Fatin, Amirah; Jamaludin, Thandar Soe Sumaiyah; Ramoo, Vimala (2018)
INTRODUCTION: Remaining involved in activities that are meaningful and purposeful and maintaining chose relationship. METHOD: Descriptive qualitative research approach. CONCLUSION: Promoting a considerate cultures in all levels of society is fundamental to create friendly and conducive environment for all people.